Characterization of cholinium-carboxylate-based aqueous biphasic systems - Almeida, Mafalda R. (2022)
In the past years large efforts have been placed in the development of novel separation techniques with improved resolution, simplicity, speed and easy to scale-up. Among these, ionic-liquid-based (IL-based) aqueous biphasic systems (ABS) have been broadly proposed for the separation of high-value compounds, allowing improved extraction performance and purification. More recently, significant efforts have been placed on the synthesis and use of novel ILs with both an acceptable environmental footprint and enhanced biocompatibility. In this sense, this work aims to characterize ABS composed of cholinium carboxylate ILs ([Ch][CnO2], with n = 2 to 7), K3PO4 and water. The respective ternary phase diagrams, including binodal curves, tie-lines and tie-line lengths, were determined at (298 ± 1) K and at atmospheric pressure. The ability to form ABS (or of the IL to be salted-out) increases with the increase of the alkyl chain length of the IL anion, up to [Ch][C5O2]; nevertheless, for longer anion alkyl chain lengths ([Ch][C6O2] and [Ch][C7O2]) the ILs self-aggregation leads to a decrease of the ILs ability to form ABS. The liquid−liquid equilibrium data experimentally determined were modeled using the local composition activity coefficient model NRTL (Non-Random Two Liquid). Finally, the partition behavior of three alkaloids (nicotine, caffeine and theobromine), used here as hydrophobicity probes, was evaluated. In all studied systems, alkaloids preferentially migrate to the IL-rich phase, with partition coefficients (K) ranging between 2.23 and complete extraction in a single-step. Furthermore, the set of ILs investigated allowed identifying an odd-even effect in the alkaloids partitioning derived from the IL anion alkyl chain length. These results support the salting-out effect exerted by K3PO4 and favorable dispersive interactions established between the IL-rich phase-forming components and the alkaloids.